Opportunistic spectrum accessing joint distance with service characteristics in IOT networks - Jun SUN; Hong-bo ZHU (Tongxin xuebao)
An accessing scheme which combines distance with service for the applications in IOT networks was proposed.First,a channel-availability list based on the distance relationship between system and non-system users was built.The list provided a priority of each channel for non-system users.Then the service-matched expression between the IOT user and the liscensed user was proposed.Based on the list and the expression,a interfrence-driven utility function was defined.Finally,the accessing scheme was optimized from the cross-layer design point of view.It was proved that the scheme guaranteed both the interference suppression and the resource sharing in IOT based on the QoS requirements.